Impacts of weaning weights and mycotoxin challenges on jejunal mucosa-associated microbiota, intestinal and systemic health, and growth performance of nursery pigs - D. M. Holanda; S. W. Kim (Journal of Animal Science and Biotechnology, 2022)
Abstract Background This study aimed at investigating the effects of mycotoxin challenge on the growth and physiology of nursery pigs with different weaning weights. Results At weaning, 10 pigs were euthanized to collect jejunal mucosa and 90 pigs were assigned following a randomized complete block design in a 2 × 2 factorial arrangement of treatments with 3 pigs per pen. Factors were: weaning weight (light: body weight, BW < 7.5 kg or heavy: BW > 9.0 kg); and dietary mycotoxins (supplementation of 0.2 mg/kg aflatoxins, 2.0 mg/kg deoxynivalenol). All diets had titanium dioxide as an external marker at 0.5%. Growth performance and fecal score were recorded until pigs achieved 20 kg BW (light pigs average BW = 21.1 kg and heavy pigs average BW = 20.5 kg). Pigs were sampled for blood, ileal digesta, jejunal tissue and mucosa at 20 kg BW. Data were analyzed using the mixed procedure of SAS. At weaning, light pigs had decreased (P < 0.05) jejunal interleukin-8, increased (P < 0.05) tumor necrosis factor-α, and increased (P < 0.05) α-diversity indexes of jejunal mucosa-associated microbiota. At 20 kg of BW, light pigs had decreased (P < 0.05) average daily gain (ADG), average daily feed intake (ADFI), and gain to feed ratio (G/F). Mycotoxins decreased (P < 0.05) BW, ADG, ADFI, and G/F. Light pigs tended to have increased fecal score on d 0 (P = 0.080), d 10 (P = 0.069), and increased (P < 0.05) fecal score at 20 kg. Mycotoxins decreased the apparent ileal digestibility of nitrogen (P < 0.05). Light pigs had increased (P < 0.05) intestinal malondialdehydes and interleukin 8. Mycotoxins tended to increase (P = 0.060) intestinal tumor necrosis factor-α. Conclusions Nursery pigs with light weaning weight were more susceptible to jejunal inflammation and had impaired intestinal health due to weaning stress, whereas mycotoxins diminished the health and growth of nursery pigs regardless of weaning weight.